HUBUNGAN PENGETAHUAN DENGAN SIKAP IBU HAMIL TENTANG DAMPAK PENYAKIT MALARIA PADA KEHAMILAN - Bahrah; Priscilla Jessica Pihahey; Yuni Subhi Isnaini; Indah Maulidia (Politeknik Kesehatan Kemenkes Sorong, 2021)
ABSTRACTAccording to the World Malaria Report in 2018 there were 228 million cases of malaria worldwide and in 2019 it reached 229 million, this indicates an increase of about 1 million cases in the world. The purpose of this study was to determine the relationship between the level of knowledge and attitudes of pregnant women about the impact of malaria on pregnancy at the Sanggeng Public Health Center, Manokwari Regency. This study used a correlational analytic method with a cross-sectional study design approach with number of samples in the study were 47 people. Data analysis used univariate analysis in the form of frequency distribution and bivariate analysis using Chi-Square (X²) statistical test using SPSS program with 95% confidence level. The results of statistical tests showed that there was no significant relationship between the level of knowledge and attitudes of pregnant women about the impact of malaria with p-value = 0.133 > 0.05 OR = 1.237. Conclusion: there is no significant relationship between the level of knowledge and attitudes of pregnant women about the impact of malaria. Pregnant women who have a low level of knowledge will have a negative attitude 1.237 times greater than mothers who have good knowledge.